Analisis Dampak Overtime Kerja terhadap Kelelahan Fisik dan Mental Crew Kapal Mv. Manalagi Tisya - Wolfgang Alexander Defara; M. Imam Firdaus; Trisnowati Rahayu; Sutoyo Sutoyo (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze the impact of overtime work on physical and mental fatigue of the crew of the MV ship. Manalagi Tisya, by identifying the causal factors and consequences that may arise due to additional working hours. In this study, the researcher will apply a qualitative research method with a descriptive approach. This research was conducted by the author on the MV ship. Manalagi Tisya owned by PT Pelayaran Manalagi which is a subsidiary of PT Salam Pacific Indonesia Lines, with the ship call sign